Asomatognosia: Structured Interview and Assessment of Visuomotor Imagery - Saetta, Gianluca; Zindel-Geisseler, Olivia; Stauffacher, Franziska; Serra, Carlo; Vannuscorps, Gilles; Brugger, Peter (Frontiers in Psychology, 2021)
Asomatognosia designates the experience that one’s body has faded from awareness. It is typically a somaesthetic experience but may target the visual modality (“asomatoscopy”). Frequently associated symptoms are the loss of ownership or agency over a limb. Here, we elaborate on the rigorous nosographic classification of asomatognosia and introduce a structured interview to capture both its core symptoms and associated signs of bodily estrangement. We additionally report the case of a pure left-sided hemiasomatognosia occurring after surgical removal of a meningioma in the right atrium. Despite the wide lesions of the right angular gyrus and of the temporo-parietal junction, the patient did not present visuospatial deficits or bodily awareness disorders other than hemiasomatognosia. The patient and 10 matched controls’ motor imagery was formally assessed with a limb laterality task in which they had to decide whether hands and feet presented under different angles of rotation depicted a left or a right limb. Bayesian statistics showed that patient’s reaction times were significantly impaired exclusively for the left foot and especially for mental rotations requiring somatomotor rather than visual limb representations. This was in accordance with a more enduring left-sided hemiasomatognosia for the lower limbs confined to the somesthetic modality. Our findings shed new light on motor imagery in asomatognosia and encourage the future use of the structured interview introduced here. In addition, the limb laterality task may capture phenomenological elements of a case by chronometric means. This allows a more standardized reporting of phenomenological detail and improves communication across different clinical facilities.